Implementation of School-Based Management - Lazwardi, Dedi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Education has an important role in influencing the advancement of a nation's civilization. A nation that has good education tends to be an advanced nation in civilization, science and technology, social economy, as well as culture. One of the educational problems is the need for adjustment and improvement of educational program material so that it can flexibly move along with the demands of the workforce and the changing demands of people's lives. The implementation of School-Based Management (SBM) is essentially the granting of greater autonomy to schools with the ultimate goal of improving the quality of the results of the implementation of education so that it can produce actual achievements through a well established managerial process. School-based management is the granting of broad autonomy at the level of the education unit in order to be able to manage resources and sources of funds and allocate according to the level of need. The aim of school-based management is to improve the efficiency of education quality by independence and flexibility in managing existing resources. Components in school-based management include management of curriculum and teaching programs, management of teaching staff, management of students, financial management and financing, management of educational facilities and infrastructure, public relations management and special service management. Supporting factors for the success of the first school-based management, the demands of a considerable democratic life from the people in the reform era. Second, the application of Law No. 22 of 1999 concerning Regional Government which emphasizes the autonomy of government at the district / city level. Third, there is a school committee that functions to help implement the Social Safety Net (JPS) program in many schools. Fourth, there is a desire by the government to increase community participation in education by increasing the duties, functions and roles of the Education Provider Assistance Agency (BP3). Factors that become obstacles in running school-based management come from students, educators, infrastructure and community participation.